Comparison of a modified 2-step insulin response test performed with porcine zinc insulin and an oral glucose test to detect hyperinsulinemic Icelandic horses - Frers, Florian; Delarocque, Julien; Huber, K.; Feige, Karsten; Warnken, Tobias (The Veterinary Journal, 2023)
Both, oral and intravenous (IV) testing protocols, are recommended and still used to detect insulin dysregulation (ID) in equids. However, IV tests mainly focus on peripheral insulin resistance (IR), while oral tests assess hyperinsulinemia (HI), which are different aspects of ID. The objective of this study was to describe if horses with HI also demonstrate IR and consequently can be detected by a modified 2-step insulin response test (2-step IRT) performed with a veterinary approved porcine zinc insulin (PZI). Twelve Icelandic horses were subjected to an OGT and 2-step IRT in a crossover study. Serum insulin concentrations during the OGT revealed that six horses were hyperinsulinemic (HI) while six were not (NON-HI). To describe the glucose response to IV injected PZI, the decline of plasma glucose concentration within the first 30 min was analyzed. Glucose reduction was similar in horses with and without HI during the 2-step IRT over time. Additionally, none of the horses reached a glucose reduction of ≥ 50% at 30 min. The results of the present study indicated that a comparable insulin mediated glucose uptake may be observed in horses with and without HI during a modified 2-step IRT. While six out of twelve horses were identified as HI by the OGT, all twelve horses were identified as IR by the modified 2-step IRT performed with PZI underlining the importance, but difficulty in choosing the right diagnostic tool in clinical settings to assess ID.